A universal SFDM halo mass for the Andromeda and Milky Way's dSphs? - Lora, Verónica (The astrophysical journal, 2015)
Dwarf spheroidal galaxies are the most common type of galaxies, and are the most dark matter (DM) dominated objects in the universe. Therefore, they are ideal laboratories to test any DM model. The Bose-Einstein condensate/scalar field DM model considers that the DM is composed by spinless-ultra-light particles which can be described by a scalar field. This model is an alternative to the Λ-cold DM model. In this work I study the kinematics of the dwarf spheroidal satellite galaxies of the Milky Way and Andromeda, under the scalar field/BEC dark matter Paradigm in two limits: when the self-interacting parameter is equal to zero, and when the self-interacting parameter is . I find that dwarf spheroidal galaxies with very high mass-to-light ratios (M/L; higher than 100) are in better agreement with an Navarro-Frenk-White mass density profile. On the other hand, dwarf spheroidal galaxies with relatively low M/L and high luminosities are better described with the SFDM model. Such results are very encouraging to further test alternative DM models using the dynamics of dwarf galaxies as a tool.
Gesehen am 03.06.2020